Persistent primitive hypoglossal artery associated with Chiari II malformation: Diagnosis and clinical implications - Gupta, Mudit (Medknow Publications, 2010)
We present a case of persistent primitive hypoglossal artery (PPHA) associated with Chiari II malformation and discuss the clinical implications. There has been one reported case of PPHA associated with Chiari 1 malformation, but none in association with Chiari II. Our patient also had a widened hypoglossal canal, with cerebrospinal fluid (CSF) sac herniation through it.